ASAL MUASAL KEMATIAN MANUSIA DAN TRADISI KUMPUL KELUARGA DALAM BUDAYA CINA - Zhang Wei (Humaniora, 2008)
This article explores the relationship between the myth ‘Chang’e Flying to the Moon’ and the subject of family reunion at Mid-autumn festival. An analysis based on Claude Levi-Strauss’ structuralist theory reveals that the fairy tale is concerned with the origin of human death in order to teach descents of a family to be good to family members as one cannot become alive again when he/she is claimed by death.